2021
DOI: 10.3390/membranes11020109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature and Flow Rate on the Cell-Free Area in the Microfluidic Channel

Abstract: Blood cell manipulation in microdevices is an interesting task for the separation of particles, by their size, density, or to remove them from the buffer, in which they are suspended, for further analysis, and more. This study highlights the cell-free area (CFA) widening based on experimental results of red blood cell (RBC) flow, suspended in a microfluidic device, while temperature and flow rate incrementally modify RBC response within the microflow. Studies of human red blood cell flow, at a concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…As previously mentioned, the use of microparticles in blood analogue fluids has been demonstrated to be essential to reproduce multiphase effects taking place in the human microcirculatory system, such as the cell-free layer (CFL) phenomena. The flow of the plasma analogue fluid (DMSO/W-PEO4M) with a 20% by volume of PDMS microparticles (45 : 1) was analyzed through a microfluidic channel with an important constriction, to simulate a microstenosis, and the results were compared with those of human blood, 55 also with a concentration of 20% by volume of RBCs. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As previously mentioned, the use of microparticles in blood analogue fluids has been demonstrated to be essential to reproduce multiphase effects taking place in the human microcirculatory system, such as the cell-free layer (CFL) phenomena. The flow of the plasma analogue fluid (DMSO/W-PEO4M) with a 20% by volume of PDMS microparticles (45 : 1) was analyzed through a microfluidic channel with an important constriction, to simulate a microstenosis, and the results were compared with those of human blood, 55 also with a concentration of 20% by volume of RBCs. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…12-a shows the design of the microfluidic device used in this study, the same as that used in Rodíguez-Villarreal et al . 55 to study the effect of temperature and the flow rate on the cell-free area. For the flow rates ( Q ) used in the in vitro experiments, this geometry gave rise to a high shear rate of around 10 4 s −1 , and allowed one to get a wide free layer of particles due to the flow inertia.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The movement of erythrocytes through blood vessels at elevated temperature is an interesting and useful task in separating blood cells from the buffer in which they are suspended based on their size or density, and for further analysis. It has been found that increasing the temperature increases the cell-free area near the blood vessel wall due to the inertia of the cell flow after the narrowing of the blood vessel [79]. The movement of erythrocytes through the blood vessel at elevated temperature in this way (increased area without cells near the blood vessel wall), enabled the production of a hybrid microfluidic device that uses hydrodynamic forces to separate human plasma from blood cells.…”
Section: Tablementioning
confidence: 99%
“…There are other applications of membranes that do not require to focus at nanoscale, since the fluid dynamics at microscale can intrinsically separate particles from the suspending fluid. Rodríguez-Villarreal [7] et al focused on the effect of temperature and flow rate to increase the efficiency of separation taking advantage of microfluidic hydrodynamics effects. The accuracy of the performance of microfluidic-based particle separators is essential to achieve an equivalent performance in point-of-care devices compared to the conventional laboratory-based analytics.…”
mentioning
confidence: 99%